Incorporating Blogging into an EFL Writing Course: An Action Research - Muhtia, Anggri; Drajati, Nur Arifah (Issues in Language Studies, 2017)
The application of blogs in English teaching and learning, especially in writing, has gained considerable attention. It combines learning activities with advanced Internet technologies and virtual social interaction. Assigning students to write online (blogging) outside classroom hours would enable students to learn in authentic social contexts and allow them to get exposed to authentic learning materials. The purpose of this study was to improve students’ writing skill through incorporating blogging activity into an EFL writing course. The blogging activity was carried out on a social network website that provides a blog section in addition to many features. The members of the website (which is part of an English learning activity) can post their writing and give comments on each other’s blog posts. In this study, mixed methods were applied in action research that integrated qualitative and quantitative data. The qualitative data were collected using observations and interviews, while the quantitative data were from test scores. The work was developed through two cycles. The findings showed that there was an improvement in students’ writing skill and students’ perceptions towards blogging were positive.